Social media and consumer awareness toward manufactured food - Jamal Ahmed Hama Kareem (Taylor & Francis Group, 2016)
Consumer awareness of the many important issues in daily life is one of the most important priorities, and this awareness liberates society from many of these problems, thereby making that society sophisticated and civilized. However, many societies, especially in developing countries, are experiencing problems in sensitizing consumers about many of the necessary everyday products, especially the manufactured food products that have become one of the basic ingredients of the meals on the table every day. Given the importance of the foregoing, the current study tried to investigate the important social issue, which is represented in the role that can be played by social media in consumer awareness toward manufactured food products in terms of health risks that can result due to the consumption of these products due to non-awareness of the dangers. To achieve this end, the quantitative method for data collection in the framework of the case study was chosen. This has been through the use of a questionnaire survey that has already been tested. The sample of the study was 351 respondents selected based on stratified sampling technique. The criteria for choosing the respondents to be part of the study were based on the full time employee of the organization. The results of the study revealed that the modern social media have a greater role than traditional social media in the consumer awareness toward manufactured food products. The study concludes with future directions for researchers interested in the area.